결혼이민자를 위한 정책현황 분석 및 개선방안 - 유진희(Jin-Hui Yu) (한국비교정부학보, 2020)
(Purpose) This study was aimed to analyze the status of policies for married immigrants and to suggest the directions of the policies for multicultural families in Korea. (Design/methodology/approach) This study is methods of current statuses of married women immigrants, regulations and systems, delivery system, and multiple policies were analyzed to review the performances by literature reviews to propose the policies for married women immigrants. Also, a variety of problems that women married immigrants experienced by literature reviews, and improvement directions of policies and implementation plans were proposed so as for married women immigrants to be able to support them practically. (Findings) It showed that people’s understanding was not sufficient on married immigrants though multiple policies and services were provided for them to be able to solve various problems that they experienced and to adapt to the society well. Social integration was not sufficient due to discrimination and exclusion for married immigrants in the society; and problems to access the supporting system for married immigrants, redundancy and inefficiency of the policies, inappropriate integrative approaches were found in terms of the policies for married immigrants. (Research implications or Originality) It is necessary to provide the required services and approach with integrative policies for married immigrants to be ultimately adapted in the society stably. First, collaboration among implementation parties should be strengthened and redundant services should be minimized between central and local governments. Also, practical services should be provided by customized services per lifecycle based on the desires and demands of married immigrants. For complicated problems of married immigrants, one-stop service system should be established, moreover, the policies for them should be established and enhanced considering them not as the special subjects but our national citizens. KCI Citation Count: 0